Cost-utility analysis of certolizumab pegol versus alternative tumour necrosis factor inhibitors available for the treatment of moderate-to-severe active rheumatoid arthritis in Spain - Hidalgo-Vega, Álvaro (Cost Eff Resour Alloc, 2015)
BACKGROUND: Certolizumab pegol, a PEGylated tumour necrosis factor (TNF)-inhibitor, improves the clinical signs and symptoms of rheumatoid arthritis (RA) when used in combination with methotrexate or as monotherapy. This study evaluatedthe cost-utility of certolizumab pegol versusTNF-inhibitors plus methotrexate in the treatment of moderate-to-severe RA in Spain. METHODS: A Markov cohort health state transition model was developed to evaluate the cost-utility (costs and quality-adjusted life years [QALYs]) of certolizumab pegol versus other TNF-inhibitors licensed in Spain in 2009. Efficacy was measured using the American College of Rheumatology (ACR) responses at 6 months, based on adjusted indirect comparisons from published clinical trials. Utilities were derived from EQ-5D data from certolizumab pegol RA clinical trials. Clinical history and resource use data came from published literature. Unit costs were taken from Spanish databases or published data (cost year 2009). Base case analyses were conducted from the payer perspective, with a lifetime horizon, 3.5 % annual discounting rates for costs and outcomes, and 3 % inflation rate for 2009 onwards. One-way sensitivity analyses were conducted. RESULTS: The average lifetime costs for certolizumab pegol, etanercept, adalimumab (every 2 weeks and weekly) and infliximab (3 mg/kg and 5 mg/kg) in combination with methotrexate were €140,971, €141,197, €139,148, €164,741, €136,961 and €152,561, respectively. The QALYs gained were 6.578, 6.462, 6.430 (for both adalimumab doses), 6.430, and 6.318 (for both infliximab doses), respectively. At a €30,000/QALY willingness-to-pay threshold, certolizumab pegol plus methotrexate dominated adalimumab weekly, etanercept, and infliximab 5 mg/kg, and was cost-effective versus adalimumab every 2 weeks and infliximab 3 mg/kg (all with methotrexate), with estimated ICERs of €12,346/QALY and €15,414/QALY, respectively. Certolizumab pegol monotherapy was more cost-effective versus adalimumab, and less expensive with similar health gains versus etanercept (6.416 QALYs vs 6.492). Univariate analysis showed ICERs to be sensitive to changes in time horizon, ACR response time point, baseline Heath Assessment Questionnaire (HAQ) score, and rate of HAQ-disability index deterioration after discontinuing treatment. CONCLUSIONS: This analysis shows that certolizumab pegol is cost-effective compared with other TNF-inhibitors recommended in Spain for the treatment of RA.